Renewable Natural Resources : Practical Lessons for Conflict-Sensitive Development - Ruckstuhl, Sandra (World Bank, Washington, DC, 2017)
This paper explores how a 'conflict and violence sensitive' framework in project assessment, design and implementation facilitates early identification and mitigation of negative consequences of competition and dispute, and promotes sustainable development over the longer term. It discusses the role of renewable resources in perpetuating conflict and violence, and distills lessons from selected development programming experiences in managing conflict risks associated with these dynamics. The study emphasizes that building capacity to productively address conflict and to improve community resilience to ecological change decreases vulnerability to violence, and improves livelihoods particularly for the world's poorest communities. The study draws on a range of development experience and specifically examines six case studies: three from the World Bank portfolio and three external to the Bank. Of the World Bank projects, the paper considers Andhra Pradesh Community Forest Management Project (India), Land Conflict and Vulnerability Pilot Project (Afghanistan), and Second Fadama Development Project (Nigeria). The paper also studies three external cases: conservation of managed indigenous areas (Ecuador) and Building the Capacity of Institut Congolais pour la Conservation de la Nature (ICCN) to Resolve and Manage Environmental Conflicts in Virunga National Park (DRC), both financed by U.S. Agency for International Development (USAID); and the Community Development Component of German Technical Cooperation's (GTZ's) Palestinian Water Program (West Bank). The concluding chapter outlines good practice and lessons learned from experience, emphasizing principals for building institutional and organizational capacity that support constructive conflict management.